Photodynamic Therapy Based on Nanoscale Metal–Organic Frameworks: From Material Design to Cancer Nanotherapeutics - Guan, Qun; Li, Yan‐An; Li, Wen‐Yan; Dong, Yu‐Bin (Chemistry, an Asian journal, 2018)
Photodynamic therapy (PDT) is a highly effective, noninvasive, highly selective method for cancer treatment. Nanoscale metal–organic frameworks (NMOFs) are a type of crystalline hybrid material composed of metal centers and organic linkers. Owing to their adjustable structure, easy modification, permanent pores, and good biocompatibility, NMOFs, as either nanophotosensitizers or photosensitizer nanocarriers, have been used in PDT. In this article, we summarize the recent progress in MOF‐based nanomaterials for tumor PDT. The MOF‐based nanomaterials might open up new avenues for the fabrication of new types of photosensitizers for PDT. Light delivery: Recent progress on metal–organic framework (MOF)‐based nanomaterials in tumor photodynamic therapy (PDT) is summarized, including design and fabrication strategies for MOF‐based PDT nanomaterials, and also the challenges faced in the use of MOF‐based PDT.